Managerial payoff and gift exchange in the field - Florian Englmaier; Stephen G. Leider (Center for Economic Studies and ifo Institute (CESifo), 2012)
We conduct a field experiment where we vary both the presence of a gift exchange wage and the effect of the worker's effort on the manager's payoff. The results indicate a strong complementarity between the initial wage gift and the agent's ability to repay the gift. We collect information on ability to control for differences and on reciprocal inclination to show that gift exchange is more effective with more reciprocal agents. We present a simple principal-agent model with reciprocal subjects that motivates our empirical findings. Our results offer an avenue to reconcile the recent conflicting evidence on the efficacy of gift exchange outside the lab; we suggest that the significance of gift exchange relations depends on details of the environment.
Keywords: C91; J33; M52; 330; incentives; reciprocity; gift exchange; field experiments; Leistungsanreiz; Lohn; Geschenk; Austauschtheorie (Soziologie); Arbeitsleistung; Managervergütung; Prinzipal-Agent-Theorie; Feldforschung